2016
DOI: 10.4067/s0034-98872016000500009
|View full text |Cite
|
Sign up to set email alerts
|

Hypovitaminosis D in Children with Hashimoto’s Thyroiditis

Abstract: Vitamin D deficiency is more common in children with HT than healthy controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 39 publications
2
15
0
3
Order By: Relevance
“…Screening for vit-D deficiency and replacement therapy if necessary has been recommended [22]. Levels of vit-D were observed to be significantly lower in children with HT [23]. A negative correlation between vit-D and TPO antibodies was found in our study.…”
Section: Discussionsupporting
confidence: 63%
“…Screening for vit-D deficiency and replacement therapy if necessary has been recommended [22]. Levels of vit-D were observed to be significantly lower in children with HT [23]. A negative correlation between vit-D and TPO antibodies was found in our study.…”
Section: Discussionsupporting
confidence: 63%
“…It should be noted, however, that the AITD group was older and had higher creatinine levels [59]. In pediatric patients with HT vs. healthy controls, a higher prevalence of VitD deficiency was also found [60][61][62][63]. However, in an analysis of pediatric patients with type 1 DM with vs. without HT, 25(OH)D levels < 20 ng/mL were found in both groups, with no difference between the two [64].…”
Section: Data In Hashimoto's Thyroiditis/chronic Autoimmune Thyroiditismentioning
confidence: 83%
“…Camurdan et al, as well as Evliyaoğlu et al, observed that children with newly diagnosed HT had significantly lower 25(OH)D 3 concentrations and higher prevalence of vitamin D deficiency (defined as 25(OH)D 3 < 15.2 ng/ml and ≤ 20 ng/ml, respectively) than healthy controls (44,54). The results were confirmed Sönmezgöz et al in a group of 136 Turkish children (68 with HT and 68 controls) (55). In the study of Evliyaoğlu et al vitamin D deficient children had more than 2 times increased risk of HT (OR 2.28, 95% CI 1.21-4.3) (44).…”
Section: Hashimoto's Thyroiditismentioning
confidence: 66%
“…In the study of Evliyaoğlu et al vitamin D deficient children had more than 2 times increased risk of HT (OR 2.28, 95% CI 1.21-4.3) (44). However, none of these studies was able to show the relationship between vitamin D deficiency and the severity of thyroid dysfunction (44,54,55). Lower calcidiol levels and higher rates of vitamin D deficiency were observed also in a study on Egyptian children with HT.…”
Section: Hashimoto's Thyroiditismentioning
confidence: 95%